2009
DOI: 10.4049/jimmunol.0900762
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Sensitizes Neonatal Hypoxic-Ischemic Brain Injury in a MyD88-Dependent Manner

Abstract: Neurological deficits in children, including cerebral palsy, are associated with prior infection during the perinatal period. Experimentally, we have shown that pre-exposure to the Gram-negative component LPS potentiates hypoxic-ischemic (HI) brain injury in newborn animals. LPS effects are mediated by binding to TLR4, which requires recruitment of the MyD88 adaptor protein or Toll/IL-1R domain-containing adapter inducing IFN-β for signal transduction. In this study, we investigated the role of MyD88 in neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
143
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 153 publications
(151 citation statements)
references
References 54 publications
7
143
1
Order By: Relevance
“…Sensitization to hypoxic-ischaemic damage following neonatal administration of LPS appears to last at least up to 3 days in rats 62 and 14 hours in mice. 59 In additional experiments, we showed that intrauterine exposure of pregnant mice to LPS resulted in increased cerebral vulnerability of pups to hypoxia-ischaemia up to 14 days postnatally. 16 However, it has become evident that within a certain time of LPS exposure the brain becomes less vulnerable or, so-called, preconditioned.…”
Section: Experimental Evidence Of Inflammation-induced Sensitization mentioning
confidence: 97%
See 3 more Smart Citations
“…Sensitization to hypoxic-ischaemic damage following neonatal administration of LPS appears to last at least up to 3 days in rats 62 and 14 hours in mice. 59 In additional experiments, we showed that intrauterine exposure of pregnant mice to LPS resulted in increased cerebral vulnerability of pups to hypoxia-ischaemia up to 14 days postnatally. 16 However, it has become evident that within a certain time of LPS exposure the brain becomes less vulnerable or, so-called, preconditioned.…”
Section: Experimental Evidence Of Inflammation-induced Sensitization mentioning
confidence: 97%
“…21,58 Administering an agent with anti-inflammatory properties, or disabling the TLR inflammatory pathway, reduced the severity of the LPS sensitization. 59,60 These studies demonstrate that exposure to inflammation prior to a moderate hypoxic-ischaemic insult is sufficient, through a sensitization process, to make the newborn brain extremely susceptible to damage.…”
Section: Inflammation-induced Sensitization Bobbi Fleiss Et Al 19 Exmentioning
confidence: 99%
See 2 more Smart Citations
“…Each hemisphere (approximately 50 mg) was sonicated in ice-cold homogenization buffer (50 mM Tris, pH 7.3, 2 mM ethylenediaminetetraacetic acid, 1% protease inhibitor cocktail [P8340; Sigma]). The homogenate was centrifuged at 10 000g for 10 minutes at 4°C, and the supernatant (S2; cytosolic fraction) was used in the determination of caspase-3 activity as described previously [26,27]. Staphylococcus epidermidis bacteremia induces systemic cytokine and brain CCL2 chemokine production 6 hours after injection.…”
Section: Caspase-3 Activity Measurementmentioning
confidence: 99%